Comorbidities between specific learning disorders and psychopathology in elementary school children in Germany - Visser, Linda; Kalmar, Julia; Linkersdörfer, Janosch; Görgen, Ruth; Rothe, Josefine; Hasselhorn, Marcus; Schulte-Körne, Gerd (Frontiers in psychiatry, 2020)
Children with reading and/or spelling disorders have increased rates of behavioral and emotional problems and combinations of these. Some studies also find increased rates of attention-deficit-/hyperactivity disorder (ADHD), conduct disorder, anxiety disorder, and depression. However, the comorbidities of e.g. arithmetic disorders with ADHD, anxiety, and depression have been addressed only rarely. The current study explored the probability of children with specific learning disorders (SLD) in reading, spelling, and/or arithmetic to also have anxiety, depression, ADHD, and/or conduct disorder. The sample consisted of 3014 German children from grades 3 and 4 (mean age 9;9 years) who completed tests assessing reading, spelling as well as arithmetic achievement and intelligence via a web-based application. Psychopathology was assessed using questionnaires filled in by the parents. In children with a SLD we found high rates of anxiety (21%), depression (28%), ADHD (28%), and conduct disorder (22%). Children with SLD in multiple learning domains had a higher risk for psychopathology and had a broader spectrum of psychopathology than children with an isolated SLD. The results highlight the importance of screening for and diagnosing psychiatric comorbidities in children with SLD.
Gesehen am 10.06.2020